Amino terminal pro brain natriuretic peptide predicts all-cause mortality in patients with chronic obstructive pulmonary disease: Systematic review and meta-analysis. (May 2017) - Pavasini, Rita; Tavazzi, Guido; Biscaglia, Simone; Guerra, Federico; Pecoraro, Alessandro; Zaraket, Fatima; Gallo, Francesco; Spitaleri, Giosafat; Contoli, Marco; Ferrari, Roberto; Campo, Gianluca
Natriuretic peptides (NPs) are a family of prognostic biomarkers in patients with heart failure (HF). HF is one of the most frequent comorbidities in patients with chronic obstructive pulmonary disease (COPD). However, the prognostic role of NP in COPD patients remains unclear. The aim of this meta-analysis was to evaluate the relation between NP and all-cause mortality in COPD patients. We performed a systematic review and meta-analysis of observational studies assessing prognostic implications of elevated NP levels on all-cause mortality in COPD patients. Nine studies were considered for qualitative analysis for a total of 2788 patients. Only two studies focused on Mid Regional-pro Atrial Natriuretic Peptide (MR-proANP) and brain natriuretic peptide (BNP), respectively, but seven studies focused on pro-BNP (NT-proBNP) and were included in the quantitative analysis. Elevated NT-proBNP values were related to increased risk of all-cause mortality in COPD patients both with and without exacerbation (hazard ratio (HR): 2.87, p < 0.0001 and HR: 3.34, p = 0.04, respectively). The results were confirmed also after meta-regression analysis for confounding factors (previous cardiovascular history, hypertension, HF, forced expiratory volume at 1 second and mean age). NT-proBNP may be considered a reliable predictive biomarker of poor prognosis in patients with COPD.